2022
DOI: 10.3389/fpls.2022.910663
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Expression Profiling of Snf2 Family Genes During Reproductive Development and Stress Responses in Rice

Abstract: Sucrose non-fermenting 2 (Snf2) protein family, as chromatin remodeling factors, is an enormous and the most diverse protein family, which contributes to biological processes of replication, transcription, and DNA repair using the energy of adenosine triphosphate (ATP) hydrolysis. The members of Snf2 family proteins have been well characterized in Arabidopsis, rice, and tomato. Although this family received significant attention, few genes were identified uniquely for their roles in mediating reproductive deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Fu et al (2012) andChen et al (2023). In a previous study, qRT-PCR analysis of 14-day-old subjected to drought stress revealed that OsCHR731 was up-regulated after 12 h of treatment(Guo et al 2022), which is consistent with our ndings.Os04g0574600 encodes ae ZOS4-12-C2H2 zinc nger protein. C2H2 zinc nger proteins play an essential role in various developmental processes in plants, such as regulating plant growth, hormone signaling, and responses to biotic and abiotic stresses (Zhang et al 2016).…”
supporting
confidence: 92%
“…Fu et al (2012) andChen et al (2023). In a previous study, qRT-PCR analysis of 14-day-old subjected to drought stress revealed that OsCHR731 was up-regulated after 12 h of treatment(Guo et al 2022), which is consistent with our ndings.Os04g0574600 encodes ae ZOS4-12-C2H2 zinc nger protein. C2H2 zinc nger proteins play an essential role in various developmental processes in plants, such as regulating plant growth, hormone signaling, and responses to biotic and abiotic stresses (Zhang et al 2016).…”
supporting
confidence: 92%
“…Among the stica, rsica, inella with clustered together, but also exhibited significant similarity to MYBs of other species. Among 23 TR classes, SNF2, playing roles in plant development, DNA repair and transcription regulation (Guo et al, 2022), was the most represented followed by PHD TR with role in histone binding, pathogen defense responses and plant development (Mouriz et al, 2015).…”
Section: Classification Of Guava Retroelementsmentioning
confidence: 99%
“…At least six genes associated with cloned alkalinity tolerance in rice have been cloned [18][19][20][21][22][23][24][25]. OsLOL5 is a rice LSD1-like-type zinc finger protein (ZFP) gene containing two C2C2 domains, similar to LSD1.…”
Section: Introductionmentioning
confidence: 99%
“…ALT1 encodes the chromatin-remodeling ATPase of the Snf2 family. Studies on the alkali-resistant mutant alt1 in rice revealed that this mutant exhibits low hydrogen peroxide levels and tolerance to methyl purpurine treatment under alkalinity stress, which can reduce the production of ROS and play a positive role in alkalinity resistance by defending against oxidative damage to improve the alkalinity tolerance of rice [25]. OsSAP is a stress-associated protein that regulates soda saline-alkalinity tolerance through reactive oxygen species (ROS) homeostasis.…”
Section: Introductionmentioning
confidence: 99%